Filter media for liquid filters and liquid filters
The filter medium, comprising specific diameter ranges for two fiber groups within the nonwoven fabric, addresses the inefficiencies of conventional filters by achieving effective submicron coarse grain removal and maintaining liquid permeability, thereby enhancing filtration accuracy.
Patent Information
- Application Number
- JP2021057012
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-03-30
AI Technical Summary
Conventional nonwoven fabric filter media struggle with efficient removal of submicron coarse grains due to wide pore size distribution and lack of uniformity, leading to increased filtration resistance and potential clogging.
A filter medium composed of organic fiber nonwoven fabric, with a first fiber group having an average diameter of 100 to 300 nm and a second fiber group with an average diameter of 1 to 8 μm, where the weight ratio of the first fiber group is 20 to 70% of the total weight, achieving an average pore diameter of 0.35 μm or less and a maximum pore diameter to average pore diameter ratio of 3.5 or less.
The proposed filter medium achieves excellent classification filtering performance for submicron coarse grains, maintaining liquid permeability while efficiently removing target coarse particles and preventing aggregation of non-target particles, thus offering improved filtration accuracy compared to conventional methods.
Smart Images

Figure 0007648421000001 
Figure 0007648421000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a filter medium for a liquid filter. [Background technology]
[0002] In the industrial field, there is a demand for technology that can effectively remove foreign matter such as aggregates and undispersed matter contained in slurries during the manufacture of semiconductors, electronics products, and chemical products. In the beverage and food industries, foreign matter removal technology using filters is also used for the purpose of clarifying raw water and sterilizing products without heating, and typically, spunbond nonwoven fabrics and meltblown nonwoven fabrics made of organic fibers (e.g., Patent No. 6390612) and polyolefin membranes have been widely used for filtering such liquids.
[0003] In recent years, with the miniaturization of devices and the thinning of coatings and films, slurries in which dispersoids on the order of nanometers are dispersed very finely and uniformly are being used, and there is an increasing need for classification filtration to reliably remove coarse particles such as undispersed matter and aggregates from the slurry. As dispersoids become finer, the target coarse particle size for removal has also reached the submicron level.
[0004] However, in conventional nonwoven fabric filter media, the pore size distribution is wide and includes pore sizes larger than the size of the target coarse particles to be removed, so there is a problem that the target coarse particles cannot be sufficiently removed. In addition, in order to reduce the pore size, a method of compacting spunbonded nonwoven fabric or meltblown nonwoven fabric by calendaring, and a method of increasing the capture rate by stacking meltblown nonwoven fabrics have been considered, but since the pore size is not uniform, it is necessary to increase the thickness of the filter material in order to maintain the filtration accuracy, and there is a concern that the filtration resistance will increase (for example, Patent Document 2, Japanese Patent No. 6560101). Although a filter material can be obtained by electrospinning in order to form a fine structure (for example, Patent Document 3, Japanese Patent Publication No. 2019-077962), due to the characteristics of the manufacturing method, the basis weight of 15 g / m 2It is difficult to obtain such a filter medium, and there is a risk that the collected material will escape to the secondary side due to the small basis weight. In addition, there is a method of using a polyolefin membrane or the like to increase the removal rate of coarse particles (for example, Patent Document 4, JP 2017-127864 A), but since the membrane filter medium has a high filter medium density and a small number of openings, there is a concern that the fine particles of the dispersed matter that are not subject to filtration in classification filtration will aggregate on the filter medium surface and become coarse particles, which is a bridge phenomenon. In addition, there is a concern that when amorphous foreign matter such as gel-like foreign matter is mixed in, a sudden blockage will occur, leading to an increase in differential pressure. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6390612 [Patent Document 2] Patent No. 6560101 [Patent Document 3] JP 2019-077962 A [Patent Document 4] JP 2017-127864 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a filter medium for liquid filters that is excellent in classification and filtration performance for coarse particles of the submicron order contained in a dispersion of particles of the nanometer order, while also providing good liquid permeability. [Means for solving the problem]
[0007] That is, the present invention is a filter material for liquid filters comprising a nonwoven fabric of organic fibers, the nonwoven fabric being composed of a first fiber group having an average fiber diameter of 100 to 300 nm and a second fiber group having an average fiber diameter of 1 to 8 μm, the weight of the first fiber group in the nonwoven fabric being 20 to 70% by weight of the total weight of the first fiber group and the second fiber group, the nonwoven fabric having an average pore size of 0.35 μm or less, and the value obtained by dividing the maximum pore size by the average pore size being 3.5 or less. Effect of the Invention
[0008] According to the present invention, it is possible to provide a filter medium for liquid filters which has excellent classification filtration performance for coarse particles of the submicron order contained in a dispersion of particles of the nanometer order, and which is also capable of achieving good liquid permeability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described in detail.
[0010] [Organic fiber nonwoven fabric] The organic fiber nonwoven fabric is composed of a first fiber group having an average fiber diameter of 100 to 300 nm and a second fiber group having an average fiber diameter of 1 to 8 μm. In the organic fiber nonwoven fabric, the weight of the fibers of the first fiber group is 20 to 70% by weight, preferably 30 to 60% by weight, more preferably 40 to 60% by weight of the total weight of the fibers of the first fiber group and the second fiber group. When the weight of the fibers of the first fiber group is 20 to 70% by weight, uniform micropores are formed in the filter layer. If the weight of the fibers of the first fiber group is less than 20% by weight, there is a risk that a coarse-dense difference occurs in the structure of the filter layer, and there is a risk that a portion where the target coarse particles are not captured is generated. On the other hand, if the weight of the fibers of the first fiber group exceeds 70% by weight, the density of the filter increases, and there is a concern that non-target particles are captured in the filter layer, causing clogging.
[0011] [Average fiber diameter of fibers in the first fiber group] The average fiber diameter of the fibers of the first fiber group is 100 to 300 nm, preferably 100 to 250 nm, and more preferably 150 to 250 nm. By using fibers with an average fiber diameter of 100 to 300 nm as the fibers of the first fiber group, it is possible to have fine pores and increase the number of openings, so that non-target particles can pass while collecting target coarse particles of the submicron order. If the average fiber diameter of the fibers of the first fiber group is less than 100 nm, there is a risk that the fibers will detach from the mesh of the papermaking net during papermaking or conversely become agglomerates, making it impossible to obtain the desired average pore diameter. If the average fiber diameter of the fibers of the first fiber group exceeds 300 nm, there is a risk that the pore diameter will increase and the collection rate of the target coarse particles will decrease.
[0012] The fiber length of the fibers of the first fiber group is preferably 0.15 to 0.4 mm. If the fiber length is less than 0.15 mm, the processability may decrease, which is not preferable. On the other hand, if the fiber length exceeds 0.4 mm, the fibers may become aggregated fiber clumps due to poor dispersibility, which may decrease the filtration efficiency and strength, which is not preferable. The ratio L / D of the fiber length L to the fiber diameter D of the fibers in the first fiber group is preferably 200-4,000, and more preferably 800-2,500.
[0013] [Average fiber diameter of fibers in the second fiber group] The average fiber diameter of the fibers of the second fiber group is 1 to 8 μm, preferably 2 to 8 μm. If the average fiber diameter of the fibers of the second fiber group is less than 1 μm, the density of the filter medium increases, and the distance between the collected particles becomes closer, which may cause a bridge phenomenon that blocks the filter medium. On the other hand, if the average fiber diameter exceeds 8 μm, the maximum pore size may increase.
[0014] The average fiber diameter was measured by taking a cross-sectional photograph of a single fiber using a transmission electron microscope (TEM) at a magnification of 30,000 times. In this case, if the TEM has a length measurement function, the length measurement function can be used for the measurement. In addition, if the TEM does not have a length measurement function, the photograph taken can be enlarged and copied, and the measurement can be performed with a ruler after taking into account the scale. In this case, if the cross-sectional shape of the single fiber is an irregular cross-section other than a circular cross-section, the diameter of the circumscribing circle of the cross-section of the single fiber is used as the fiber diameter.
[0015] [Average pore size of nonwoven fabric] The average pore size of the organic fiber nonwoven fabric is preferably 0.35 μm or less, and the value obtained by dividing the maximum pore size by the average pore size is preferably 3.5 or less. In order to stabilize the filtration flow rate, it is necessary to pass non-target particles to the secondary side, and it is essential to maintain the voids in the nonwoven fabric during treatment. By setting the average pore size and the value obtained by dividing the maximum pore size by the average pore size within the above ranges, the probability of target coarse particles flowing out to the secondary side can be reduced.
[0016] [Porosity of nonwoven fabric] The porosity of the organic fiber nonwoven fabric is preferably 70-80%. If the porosity is less than 70%, the pressure loss increases and the filtration flow rate decreases, and in addition, the bridge phenomenon occurs frequently, in which non-target particles are packed and aggregated on the surface or inside of the filter medium, causing blockage of the filter medium. On the other hand, if the porosity exceeds 80%, large gaps are generated in the filter medium, causing a decrease in the target coarse particle removal rate. By setting the porosity to 70-80%, the removal rate can be stably maintained while reducing the pressure loss during filtration. In order to create gaps in the nonwoven fabric, a method of mixing relatively thick fibers has been used in the past, but in the present invention, the above porosity and filter medium strength can be obtained by using a second fiber group with an average fiber diameter of 1-8 μm in combination with a first fiber group.
[0017] [Thickness of nonwoven fabric] The thickness of the organic fiber nonwoven fabric is preferably 0.01-0.1 mm. If the thickness of the filter material exceeds 0.1 mm, it is not preferable that the filter material cannot secure a sufficient filtering area when storing the filter material in the cartridge protector or capsule shell, and the filter life may be shortened. On the other hand, if the thickness is less than 0.01 mm, it is not preferable that the handling property is deteriorated.
[0018] [Wet-processed nonwoven fabric] The organic fiber nonwoven fabric is preferably a wet-laid nonwoven fabric, which is preferred because it has less variation in properties related to filter performance, such as basis weight, fiber diameter, and air permeability, and is excellent in filtration efficiency, compared to nonwoven fabrics produced by a spunbonding method, a meltblowing method, an electrospinning method, or the like.
[0019] [Filter density, mesh size, Gurley air permeability] The density of the liquid filter medium of the present invention is preferably 0.3 to 0.6 g / cm 3 The density is 0.3g / cm 3 If the density is less than 0.6 g / cm3, the handling property may become poor, which is not preferable. 3 If it exceeds this value, it may become difficult to obtain a high filtration throughput, which is undesirable.
[0020] The basis weight of the filter medium for liquid filters of the present invention is preferably 10 to 30 g / m 2 With a basis weight in this range, it is possible to reduce the probability of target particles leaking out and obtain a high flow rate. The Gurley air permeability of the liquid filter material of the present invention is preferably 20 sec / 100 cc or less. If it exceeds 20 sec / 100 cc, the liquid resistance during filtration is large, which is undesirable since a sufficient amount of the liquid may not be processed.
[0021] [Filter material shape] The filter material for liquid filters of the present invention is in the form of a cartridge or capsule. For example, it is preferable that the filter medium is cylindrical and the filter medium for liquid filters is arranged in a pleated shape between the core material of the innermost layer and the protector of the outermost layer. In this case, the pleat folding pitch (distance between the peak and the valley) is preferably within a range of 5 to 30 mm. In addition, the diameter of the core material is preferably within a range of 10 to 200 mm. According to the present invention, there is provided a cartridge-type or capsule-type liquid filter using the above-mentioned liquid filter medium as a filter medium.
[0022] [First fiber group fibers] The fibers of the first fiber group are fibers of a thermoplastic resin, and examples of such fibers include polyester fibers, polyphenylene sulfide fibers, polypropylene fibers, polyethylene fibers, and aliphatic polyamide fibers. Among these, polyester fibers and polypropylene fibers are preferred.
[0023] Examples of polyesters forming polyester fibers include polyethylene terephthalate (hereinafter sometimes referred to as "PET"), polytrimethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Other examples include copolymers with aromatic dicarboxylic acids such as isophthalic acid and metal salts of 5-sulfoisophthalic acid, aliphatic dicarboxylic acids such as adipic acid and sebacic acid, hydroxycarboxylic acid condensates such as ε-caprolactone, and glycol components such as diethylene glycol, trimethylene glycol, tetramethylene glycol, and hexamethylene glycol.
[0024] The polyester may be a polyester that has been material recycled or chemically recycled, or a polyethylene terephthalate that is obtained by using a monomer component obtained from biomass, i.e., a biologically derived substance, as described in JP-A-2009-091694, or may be a polyester obtained by using a catalyst containing a specific phosphorus compound and a titanium compound, as described in JP-A-2004-270097 and JP-A-2004-211268.
[0025] In the case of polyester fibers, the polyester fibers may be any of drawn yarns, undrawn yarns, and semi-drawn yarns. The elongation may be less than 60% or 60% or more. The elongation of drawn polyester yarns is usually less than 60%, and the elongation of undrawn polyester yarns is usually 60% or more.
[0026] When using polyphenylene sulfide fiber, the following can be used as the polyarylene sulfide forming the fiber. That is, it is composed of p-phenylene sulfide unit, m-phenylene sulfide unit, o-phenylene sulfide unit, phenylene sulfone unit, phenylene sulfide ketone unit, phenylene sulfide ether unit, diphenylene sulfide unit, phenylene sulfide unit containing a substituent, and phenylene sulfide unit containing a branched structure. Among them, it is preferable to contain 70 mol% or more, particularly 90 mol% or more of p-phenylene sulfide unit, and poly(p-phenylene sulfide) is particularly preferable.
[0027] The polyphenylene sulfide fiber may be any of drawn yarn, undrawn yarn, and semi-drawn yarn. The elongation may be less than 60% or more than 60%. The polyphenylene sulfide drawn yarn usually has an elongation of less than 60%, and the polyphenylene sulfide undrawn yarn usually has an elongation of 60% or more.
[0028] [Method for producing fibers of the first fiber group] The fibers of the first fiber group can be obtained by a known method, but are preferably produced by the method disclosed in WO 2005 / 095686 or WO 2008 / 130019. That is, the fibers are preferably produced by subjecting a composite fiber having island components made of a fiber-forming thermoplastic polymer and a sea component made of a polymer (hereinafter sometimes referred to as "easily soluble polymer") that is more easily soluble in an alkaline aqueous solution than the fiber-forming thermoplastic polymer to an alkali weight reduction process to dissolve and remove the sea component.
[0029] Here, when the dissolution rate ratio of the polymer readily soluble in an aqueous alkali solution forming the sea component to the fiber-forming thermoplastic polymer forming the island components is 200 or more (preferably 300 to 3000), good island separability is obtained, which is preferable.
[0030] As the easily soluble polymer forming the sea component, polyesters, aliphatic polyamides, and polyolefins such as polyethylene and polystyrene, which have particularly good fiber forming properties, can be given as preferred examples. More specifically, polylactic acid, ultra-high molecular weight polyalkylene oxide condensation polymers, and copolymer polyesters of polyalkylene glycol compounds and 5-sodium sulfoisophthalic acid are preferred because they are easily soluble in an alkaline aqueous solution. Here, the alkaline aqueous solution refers to an aqueous solution of potassium hydroxide or sodium hydroxide. In addition, as combinations of the sea component and a solution that dissolves the sea component, formic acid for aliphatic polyamides such as nylon 6 and nylon 66, trichloroethylene for polystyrene, hydrocarbon solvents such as hot toluene and xylene for polyethylene (particularly high-pressure low-density polyethylene and linear low-density polyethylene), and hot water for polyvinyl alcohol and ethylene-modified vinyl alcohol polymers can be given as examples.
[0031] Among polyester-based polymers, a polyethylene terephthalate-based copolymer polyester having an intrinsic viscosity of 0.4 to 0.6, which is obtained by copolymerizing 6 to 12 mol % of 5-sodium sulfoisophthalic acid with 3 to 10 wt % of polyethylene glycol having a molecular weight of 4000 to 12000, is preferred. Here, 5-sodium sulfoisophthalic acid contributes to improving hydrophilicity and melt viscosity, and polyethylene glycol (PEG) improves hydrophilicity. In addition, the larger the molecular weight of PEG, the more hydrophilic it is thought to be due to its higher-order structure. However, since the reactivity becomes poor and the mixture becomes a blend system, problems may occur in terms of heat resistance and spinning stability. In addition, if the amount of copolymerization is 10 wt % or more, the melt viscosity may decrease.
[0032] On the other hand, the poorly soluble polymer forming the island components is a polymer that finally forms nanofibers, and suitable examples thereof include polyamides, polyesters, polyolefins, polyphenylene sulfide (PPS), etc. Specifically, in applications requiring mechanical strength and heat resistance, preferred polyesters include polyethylene terephthalate (hereinafter sometimes referred to as "PET"), polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and copolymers having these as main repeating units with aromatic dicarboxylic acids such as isophthalic acid and 5-sulfoisophthalic acid metal salt, aliphatic dicarboxylic acids such as adipic acid and sebacic acid, hydroxycarboxylic acid condensates such as ε-caprolactone, and glycol components such as diethylene glycol, trimethylene glycol, tetramethylene glycol, and hexamethylene glycol. Preferred polyamides include aliphatic polyamides such as nylon 6 and nylon 66. On the other hand, polyolefins have the characteristics that they are not easily affected by acids or alkalis, and that they can be used as a binder component after being extracted into nanofibers due to their relatively low melting points, and preferred examples include high density polyethylene, medium density polyethylene, high pressure low density polyethylene, linear low density polyethylene, isotactic polypropylene, ethylene propylene copolymer, and ethylene copolymers of vinyl monomers such as maleic anhydride. In particular, polyesters such as polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene terephthalate isophthalate with an isophthalic acid copolymerization rate of 20 mol% or less, and polyethylene naphthalate, and aliphatic polyamides such as nylon 6 and nylon 66 have heat resistance and mechanical properties due to their high melting points, and are therefore preferred for applications requiring heat resistance and strength compared to ultrafine fibrillated fibers made of polyvinyl alcohol / polyacrylonitrile blended spun fibers. The cross section of the island components is not limited to a round cross section, and may be a triangular cross section, a flat cross section, or another irregular cross section.
[0033] The polymer forming the sea part and the polymer forming the island parts may contain various additives, such as organic fillers, antioxidants, heat stabilizers, light stabilizers, flame retardants, lubricants, antistatic agents, rust inhibitors, crosslinking agents, foaming agents, fluorescent agents, surface smoothing agents, surface gloss improvers, and release improvers such as fluororesins, as necessary, within the limits not affecting the spinnability and the physical properties of the nanofibers after extraction.
[0034] In the islands-in-sea type composite fiber, the melt viscosity of the sea part during melt spinning is preferably higher than that of the island part polymer. When such a relationship is satisfied, even if the composite weight ratio of the sea part is reduced to less than 40%, bonding between islands is easily prevented.
[0035] The melt viscosity ratio (sea / island) is preferably in the range of 1.1 to 2.0, particularly 1.3 to 1.5. If this ratio is less than 1.1, the island components tend to bond together during melt spinning, while if it exceeds 2.0, the viscosity difference is too large and the spinning condition tends to deteriorate.
[0036] Next, the number of islands is preferably 100 or more (more preferably 500 to 2000). The sea-island composite weight ratio (sea:island) is preferably in the range of 20:80 to 80:20. This range is preferable because it makes it possible to reduce the thickness of the sea component between islands, which facilitates dissolution and removal of the sea component and makes it easy to convert the island components into nanofibers. If the proportion of the sea component exceeds 80%, the thickness of the sea component becomes too thick, while if it is less than 20%, the amount of the sea component becomes too small, which may easily cause bonding between the islands.
[0037] As the spinneret used for melt spinning, any type can be used, such as one having a group of hollow pins or a group of fine holes (pinless) for forming island components. For example, a spinneret may be used in which the island components extruded from the hollow pins or fine holes are joined with a sea component flow, the flow path of which is designed to fill the gaps between the island components, and the resulting mixture is compressed to form an islands-in-sea cross section. The extruded islands-in-sea composite fiber is solidified by cooling air and taken up by a rotating roller or an ejector set at a predetermined take-up speed to obtain an undrawn yarn (preferably having a birefringence Δn of 0.05 or less). The take-up speed is not particularly limited, but is preferably 200 to 5000 m / min. If it is less than 200 m / min, the productivity may decrease. If it is more than 5000 m / min, the spinning stability may decrease.
[0038] The obtained fibers may be directly subjected to a cutting process or a subsequent extraction process depending on the use and purpose of the ultrafine fibers obtained after extracting the sea component, or may be subjected to a cutting process or a subsequent extraction process via a drawing process or a heat treatment process to achieve the desired strength, elongation, and heat shrinkage properties. The drawing process may be a separate drawing method in which spinning and drawing are performed in separate steps, or a straight drawing method in which drawing is performed immediately after spinning in one process may be used.
[0039] Next, the composite fiber is cut so that the ratio L / D of the fiber length L to the island diameter D is, for example, 100 to 2500. The cutting is preferably performed by bundling the composite fiber into a tow of several tens to several millions of fibers and cutting the tow with a guillotine cutter or a rotary cutter.
[0040] The fiber having the above fiber diameter D is obtained by subjecting the composite fiber to an alkaline weight reduction process. In this case, the ratio of fiber to alkaline solution (bath ratio) in the alkaline weight reduction process is preferably 0.1 to 5% by weight, more preferably 0.4 to 3% by weight. If the ratio is less than 0.1% by weight, there is a high contact between the fiber and the alkaline solution, but the processability such as drainage may become difficult. On the other hand, if the ratio is 5% by weight or more, the amount of fiber is too large, and there is a risk of entanglement of the fibers during the alkaline weight reduction process. The bath ratio is defined by the following formula. Bath ratio (%) = (fiber mass (gr) / alkaline aqueous solution mass (gr) x 100)
[0041] The treatment time for the alkali weight reduction is preferably 5 to 60 minutes, more preferably 10 to 30 minutes. If it is less than 5 minutes, the alkali weight reduction may be insufficient. On the other hand, if it exceeds 60 minutes, the island component may also be reduced in weight.
[0042] In the alkali weight reduction process, the alkali concentration is preferably 2 to 10% by weight. If it is less than 2% by weight, there is a risk that the alkali is insufficient and the weight reduction rate becomes extremely slow. On the other hand, if it exceeds 10% by weight, the alkali weight reduction proceeds too quickly and the island parts may also be reduced in weight.
[0043] Furthermore, after the alkali weight reduction process, it is preferable to apply a dispersant (for example, Model YM-81 manufactured by Takamatsu Oil Co., Ltd.) to the fiber surface in an amount of 0.1 to 5.0% by weight based on the fiber weight in order to increase the dispersibility of the fibers. The cutting step and the alkali weight reduction step may be carried out in the reverse order, that is, the alkali weight reduction step may be carried out first, and then the cutting step may be carried out.
[0044] [Fibers of the second fiber group] The fibers of the second group of fibers are made of a thermoplastic resin, and are preferably polyester, polyamide or polypropylene fibers. The second fiber group preferably contains heat-fusible fibers. In this case, the content of the heat-fusible fibers in the second fiber group is, for example, 20% by weight or more, preferably 30 to 100% by weight, based on the total weight of the fibers in the second fiber group.
[0045] Of the heat-fusible fibers, the undrawn yarn is preferably an undrawn polyester fiber spun at a spinning speed of 600 to 1500 m / min. Examples of polyester include polyethylene terephthalate, polytrimethylene terephthalate, and polybutylene terephthalate. For reasons of productivity, dispersibility in water, etc., polyethylene terephthalate and copolymer polyesters mainly composed of polyethylene terephthalate are preferable.
[0046] Among the thermally adhesive fibers, preferred conjugated fibers are core-sheath type conjugated fibers in which a polymer component that exhibits a fusion adhesion effect depending on the dryer temperature during papermaking, such as a non-crystalline copolymer polyester, is arranged in the sheath, and another polymer having a melting point 20° C. or more higher than these polymers is arranged in the core. Eccentric core-sheath type conjugated fibers, side-by-side type conjugated fibers, and other configurations can also be used.
[0047] Here, from the viewpoint of cost, it is preferable that the non-crystalline copolyester contains terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol as main components.
[0048] [Method of manufacturing nonwoven fabric] As a method for producing a wetlaid nonwoven fabric, it is preferable to make paper using a normal fourdrinier paper machine, short wire paper machine, cylinder paper machine, etc., and then heat treat the paper to thermally bond the nanofibers with heat-fusible fibers. In this case, the heat treatment process can be performed using either a Yankee dryer or an air-through dryer after the papermaking process. In addition, after the heat treatment, calendaring / embossing with a metal / metal roller, metal / paper roller, metal / elastic roller, etc. may be performed. Each layer may be wetlaid and then laminated, or multiple layers may be made. EXAMPLES
[0049] The following describes the present invention by way of examples. Note that weight percent may be abbreviated as "wt%."
[0050] (1) Average fiber diameter A transmission electron microscope (TEM) (with length measurement function) was used to take a cross-sectional photograph of the fiber at a magnification of 30,000 times and measure the fiber diameter. The diameter of the circumscribed circle in the cross section of a single fiber was used as the fiber diameter. The average value of n=5 was used as the average fiber diameter.
[0051] (2) Average fiber length The ultrafine short fibers (short fibers A) before dissolving and removing the sea component were laid on a substrate and the fiber length L was measured at 20 to 500 magnifications using a scanning electron microscope (SEM). The fiber length L was measured using the length measurement function of the SEM. The average value of the n number of 5 was taken as the average fiber length.
[0052] (3) Eye count The basis weight was measured based on JIS P8124 (method of measuring the metric basis weight of paper).
[0053] (4) Thickness The thickness was measured based on JIS P8118 (Method of measuring thickness and density of paper and paperboard). The measurement load was 75g / cm 2 The average value of the five measurements was calculated and used as the thickness.
[0054] (5) Gurley air permeability Measurement was performed based on JIS P8117 (air permeability test method for paper and paperboard).
[0055] (6) Melt Viscosity The polymer after drying was set in an orifice set at the ruder temperature during spinning, and kept molten for 5 minutes. After that, it was extruded under several load levels, and the shear rate and melt viscosity at that time were plotted. Based on that data, a shear rate-melt viscosity curve was created, and the melt viscosity curve for a shear rate of 1000 sec -1 The melt viscosity was read at this time.
[0056] (7) Average pore diameter, maximum pore diameter Measurements were taken using a Perm Porometer manufactured by PMI.
[0057] (8) SiO2 slurry filtration rate The filtration rate was measured when a mixture of SiO2 slurry (weight concentration 10%) adjusted to an average particle size of 450 nm and a slurry (weight concentration 10%) adjusted to an average particle size of 20 nm was passed through a φ47 mm filter medium in a ratio of 100:1.
[0058] (9) SiO2 slurry turbidity removal rate A 100:1 mixture of SiO2 slurry (weight concentration 10%) adjusted to an average particle size of 450 nm and a slurry (weight concentration 10%) adjusted to an average particle size of 15 nm was passed through a φ47 mm filter medium, and the turbidity before and after filtration was measured using a portable turbidity system CT100 manufactured by CEM Corporation.
[0059] (10) Peak ratio of particle size distribution of filtered SiO2 slurry A 100:1 mixture of SiO2 slurry (weight concentration 10%) adjusted to an average particle size of 450 nm and a slurry (weight concentration 10%) adjusted to an average particle size of 15 nm was passed through a φ47 mm filter medium, and the particle size distribution in the liquid before and after filtration was measured using a Malvern Zetasizer Nano, and the peak ratios of particle sizes around 15 nm and 450 nm were read. The 15 nm peak ratio of the liquid before filtration was 20%, and the 450 nm peak ratio was 79%.
[0060] (11) Membrane filtration rate of filtered SiO2 slurry A SiO2 slurry (weight concentration 10%) adjusted to an average particle size of 450 nm and a slurry (weight concentration 10%) adjusted to an average particle size of 15 nm were mixed in a ratio of 100:1 and passed through a φ47 mm filter medium. The filtered liquid was then passed through a Millipore φ47 mm hydrophilic PVDF membrane filter (filtration accuracy 0.22 μm) to measure the filtration rate.
[0061] Example 1 Using polyethylene terephthalate for the island component and modified polyethylene terephthalate copolymerized with 4% by weight of polyethylene glycol and 9% by mol of 5-sodium sulfoisophthalic acid for the sea component, an islands-in-sea composite undrawn yarn with a sea:island ratio of 50:50 and the number of islands of 1440 was melt spun at a spinning temperature of 290°C and a spinning speed of 1000 m / min and wound up once. The undrawn yarn obtained was roller-drawn at a draw ratio of 4.0 times, then heat-set at 180°C and wound up as an islands-in-sea composite drawn yarn. This was cut to a fiber length of 0.2 mm and reduced in weight with alkali to obtain nanofiber A with an average fiber diameter of 200 nm.
[0062] The nanofiber A was mixed as the first fiber group at 60 wt% relative to the weight of the filter medium, and low-melting polyethylene terephthalate fibers (non-nanofiber B) with a fineness of 0.2 dtex (average fiber diameter 4.3 μm) and fiber length of 3 mm were mixed as the second fiber group at 40 wt% relative to the weight of the filter medium to prepare a slurry. Using the above, an appropriate amount of dispersant and defoamer were added, and the dispersed slurry was wet-formed into paper, which was then dehydrated with nip rollers and wound up. The paper was then introduced into a belt dryer while being unwound, and a network was formed between the binders by heat shrinkage to fix the structure, after which it was wound up with a constant tension and the basis weight was 19.0 g / m. 2 The thickness of the nonwoven fabric filter material produced by the above method was 0.047 mm and the density was 0.408 g / cm 3 The porosity was 70%. The average pore size of the nonwoven fabric filter material was 0.24 μm, and the maximum pore size was 0.62 μm. The filtration rate of the SiO2 slurry of the liquid filter filter material obtained by stacking two sheets of the obtained nonwoven fabric filter material was 1.40 mL / min, the turbidity removal rate was 95%, and the 15 nm peak ratio was 98%. The filtration rate when the SiO2 slurry was filtered through a membrane after filtration was 234.4 mL / min. The results are shown in Table 2.
[0063] Example 2 A polyethylene terephthalate fiber (non-nanofiber C) having a fineness of 0.6 dtex (average fiber diameter 7.4 μm) × fiber length of 5 mm was added to the second fiber group of Example 1, the nanofiber A was blended in an amount of 60 wt % relative to the weight of the filter medium, and the second fiber group, which is the sum of non-nanofiber B and non-nanofiber C, was blended in an amount of 40 wt % relative to the weight of the filter medium to prepare a slurry. The slurry was then made in the same manner as in Example 1 to obtain a basis weight of 19.8 g / m 2 The thickness of the nonwoven fabric filter material produced by the above method was 0.055 mm, and the density was 0.362 g / cm 3 The porosity was 73%. The average pore size of the nonwoven fabric filter material was 0.28 μm, and the maximum pore size was 0.79 μm (Table 1). The filtration rate of the SiO2 slurry of the liquid filter filter material obtained by stacking two sheets of the obtained nonwoven fabric filter material was 1.47 mL / min, the turbidity removal rate was 92%, the 15 nm peak ratio was 85%, and the filtration rate when the SiO2 slurry was filtered through a membrane after filtration was 230.8 mL / min. The results are shown in Table 2.
[0064] Example 3 The blending ratio of the first fiber group used in Example 1 was 40 wt% based on the filter medium weight. In addition, as the second fiber group, a slurry was prepared by blending polyethylene terephthalate fibers (non-nanofibers D) with a fineness of 0.06 dtex (average fiber diameter 2.4 μm) × fiber length of 0.3 mm and the non-nanofibers B in a total amount of 60 wt% based on the filter medium weight, and paper was made in the same manner as in Example 1 to obtain a paper with a basis weight of 21.8 g / m 2 The nonwoven fabric filter material was obtained by the above method. The thickness of the nonwoven fabric filter material is 0.054 mm and the density is 0.401 g / cm 3 The porosity was 70%. The average pore size of the nonwoven fabric filter material was 0.30 μm, and the maximum pore size was 0.97 μm (Table 1). The filtration rate of the SiO2 slurry of the liquid filter filter material obtained by stacking two sheets of the obtained nonwoven fabric filter material was 1.60 mL / min, the turbidity removal rate was 90%, the 15 nm peak ratio was 69%, and the filtration rate when the SiO2 slurry was filtered through a membrane after filtration was 194.8 mL / min. The results are shown in Table 2.
[0065] Comparative Example 1 The blending ratio of the first fiber group used in the above Example 1 was 30 wt% relative to the filter medium weight. In addition, as the second fiber group, a slurry was prepared in which a polyethylene terephthalate fiber (non-nanofiber E) having a fineness of 1.7 dtex (average fiber diameter 12.6 μm) × fiber length of 5 mm and a low melting point polyethylene terephthalate fiber (non-nanofiber F) having a fineness of 1.7 dtex (average fiber diameter 12.6 μm) × fiber length of 5 mm were blended to a total of 70 wt% relative to the filter medium weight (the weight ratio of non-nanofiber E to non-nanofiber F was 4:3), and paper was made in the same manner as in Example 1 to obtain a slurry having a basis weight of 29.3 g / m 2 The thickness of the nonwoven fabric filter material produced by the above method was 0.110 mm, and the density was 0.266 g / cm 3 The porosity was 80%. The average pore size of the nonwoven fabric filter material was 0.45 μm, and the maximum pore size was 3.21 μm (Table 1). The filtration rate of the SiO2 slurry of the liquid filter filter material obtained by stacking two sheets of the obtained nonwoven fabric filter material was 5.98 mL / min, the turbidity removal rate was 19%, the 15 nm peak ratio was 28%, and the filtration rate when the SiO2 slurry was filtered through a membrane after filtration was 2.9 mL / min. The results are shown in Table 2.
[0066] Comparative Example 2 Nanofiber G having an average fiber diameter of 700 nm and a fiber length of 0.5 mm was added to the first fiber group used in Example 1 above, and the first fiber group was prepared by mixing the nanofiber A and the nanofiber G in such a way that the total weight of the first fiber group was 30 wt % of the weight of the nonwoven fabric filter material (the weight ratio of nanofiber A to nanofiber G was 1:1), and the second fiber group was prepared by mixing the non-nanofiber B and the non-nanofiber D in such a way that the total weight of the second fiber group was 70% (the weight ratio of non-nanofiber B to non-nanofiber D was 3:4). A slurry was prepared by papermaking in the same manner as in Example 1, resulting in a basis weight of 29.5 g / m 2 The thickness of the nonwoven fabric filter material produced by the above method was 0.071 mm, and the density was 0.414 g / cm 3The porosity was 70%. The average pore size of the nonwoven fabric filter material was 0.73 μm, and the maximum pore size was 2.15 μm (Table 1). The filtration rate of the SiO2 slurry of the liquid filter filter material obtained by stacking two sheets of the obtained nonwoven fabric filter material was 37.9 mL / min, the turbidity removal rate was 6%, the 15 nm peak ratio was 21%, and the filtration rate when the SiO2 slurry was filtered through a membrane after filtration was 3.5 mL / min. The results are shown in Table 2.
[0067] Comparative Example 3 In Example 1, the nanofibers A were changed to nanofibers H having an average fiber diameter of 400 nm and a fiber length of 0.4 mm, and the nanofibers H were blended as the first fiber group so as to be 60 wt% relative to the weight of the filter medium, and unstretched polyethylene terephthalate having an average fiber diameter of 1.2 μm and 0.4 mm (non-nanofibers I) as the second fiber group and the non-nanofibers B were blended so as to be 40 wt% in total relative to the weight of the filter medium (the weight ratio of non-nanofibers I and non-nanofibers B was 1:1). A slurry was prepared, and paper was made in the same manner as in Example 1 to obtain a basis weight of 20.7 g / m. 2 The thickness of the nonwoven fabric filter material produced by the above method was 0.044 mm, and the density was 0.475 g / cm 3 The porosity was 65%. The average pore size of the nonwoven fabric filter material was 0.45 μm, and the maximum pore size was 1.18 μm (Table 1). The filtration rate of the SiO2 slurry of the liquid filter filter material obtained by stacking two sheets of the obtained nonwoven fabric filter material was 4.10 mL / min, the turbidity removal rate was 25%, the 15 nm peak ratio was 27%, and the filtration rate when the SiO2 slurry was filtered through a membrane after filtration was 2.9 mL / min. The results are shown in Table 2.
[0068] Comparative Example 4 A commercially available hydrophilic PVDF membrane filter (precision: 0.22 μm) was prepared. The basis weight of this membrane filter was 74 g / m 2 , the thickness is 0.130 mm, and the density is 0.573 g / cm 3The porosity was 68%. The average pore size was 0.20 μm, and the maximum pore size was 0.46 μm (Table 1). When the above membrane filter was used, the filtration rate of the SiO2 slurry was 1.67 mL / min, the turbidity removal rate was 94%, the 15 nm peak ratio was 92%, and the filtration rate when the SiO2 slurry was subjected to membrane filtration after filtration was 182.9 mL / min. The results are shown in Table 2.
[0069] [Table 1]
[0070] [Table 2]
[0071] The results shown in Table 2 are explained below. In Examples 1 to 3, the turbidity removal rate of the SiO2 slurry was 90% or more, the 15 nm peak ratio was approximately 70% or more, and the 450 nm peak ratio was reduced to 25% or less. In addition, the filtration rate when the SiO2 slurry was subjected to membrane filtration after filtration exceeded 190 mL / min, which showed good results indicating that the coarse particles (particle size 450 nm) in the slurry were effectively removed. In Comparative Example 1, nanofibers with a fiber diameter of 200 nm were used, but the fiber diameter of the non-nanofibers in the second fiber group exceeded 8 μm, so the maximum pore size of the filter medium increased, the turbidity removal rate was low, and the 450 nm peak ratio did not decrease. The filtration rate when the SiO2 slurry was subjected to membrane filtration after filtration was significantly small, which also showed that the removal performance of coarse particles was low. In Comparative Example 2, the ratio of nanofibers A with a fiber diameter of 200 nm in the first fiber group was set to 20% or less, so the removal performance decreased. In Comparative Example 3, the first fiber group was made of fibers having an average fiber diameter of more than 300 nm, and non-nanofiber I having a fiber diameter of 1.2 μm was used to improve the filtration accuracy, but the porosity was 70% or less, and the filtration rate decreased. In addition, the removal performance was not improved. In Comparative Example 4, a similar filtration test was carried out using a commercially available membrane filter, and the filtration rate and turbidity removal rate of the SiO2 slurry were equivalent to those of Examples 1 to 3 of the present invention, and the filtration rate when the SiO2 slurry was subjected to membrane filtration after filtration was higher in Examples 1 to 3 of the present invention. From the above, it has been shown that a filter medium composed of nanofiber A having an average fiber diameter of 100 to 300 nm and a second fiber group which is a non-nanofiber having an average fiber diameter of 1 to 8 μm, and in which the weight ratio of the first fiber group is within the range of 20 to 70% of the filter medium weight, maintains a fine and uniform structure with an average pore diameter of 0.35 μm or less and a value obtained by dividing the maximum pore diameter by the average pore diameter of 3.5 or less, while still maintaining a porous structure. Therefore, when a mixture of target coarse particles to be removed on the submicron order and non-target particles on the nanometer order is filtered, the filter medium has excellent classification filtration performance in which the target coarse particles are efficiently captured while allowing the non-target particles to pass through, and filtration processing can be performed while preventing the aggregation of non-target particles, thereby providing filtration accuracy equivalent to or greater than that of a membrane filter. [Industrial Applicability]
[0072] The filter medium for liquid filters of the present invention and the liquid filter using the same are suitable for use in collecting submicron coarse particles such as agglomerates contained in slurries in which nanometer-order particles are dispersed, such as polishing slurries and semiconductor processes, but may also be used in manufacturing processes for industrial products such as foods, beverages, pharmaceuticals, and electronic materials.
Claims
1. A filter material for liquid filters, comprising a nonwoven fabric of organic fibers, the filter material being formed by laminating a plurality of sheets of the nonwoven fabric of organic fibers, the nonwoven fabric having a thickness of 0.01 to 0.1 mm, the nonwoven fabric being composed of a first fiber group having an average fiber diameter of 100 to 300 nm and a second fiber group having an average fiber diameter of 1 to 8 μm, the weight of the first fiber group in the nonwoven fabric being 20 to 70% by weight of the total weight of the first fiber group and the second fiber group, the nonwoven fabric having an average pore size of 0.35 μm or less, and the value obtained by dividing the maximum pore size by the average pore size being 3.5 or less.
2. 2. The filter material for liquid filters according to claim 1, wherein the nonwoven fabric has a porosity of 70 to 80%.
3. 3. The filter material for liquid filters according to claim 1, which has a Gurley air permeability of 20 seconds / 100 cc or less.
4. The filter medium for liquid filters according to any one of claims 1 to 3, wherein the first fiber group is made of polyester fibers and / or polypropylene fibers.
5. The filter medium for liquid filters according to any one of claims 1 to 4, wherein the second fiber group is made of polyester fibers, polyamide fibers or polypropylene fibers.
6. 6. The filter medium for liquid filtration according to claim 5, wherein the second group of fibers comprises heat-fusible fibers.
7. The filter medium for liquid filters according to claim 6, wherein the nonwoven fabric is a wet-laid nonwoven fabric.
8. A cartridge-type or capsule-type liquid filter using the liquid filter material according to any one of claims 1 to 7 as a filter material.
Citation Information
Patent Citations
Catalyst converter
JP1988090612A
Filter medium for fine particles
JP1995024231A
Cartridge filter for liquid filtration
JP2010167384A
Filter medium and structure
JP2012050985A
Polyamide ultrafilter membrane having organic solvent tolerance and manufacturing method for the same
JP2017127864A